An Energy Box in a Cloud-Based Architecture for Autonomous Demand Response of Prosumers and Prosumages - Brusco, Giovanni; Burgio, Alessandro; Menniti, Daniele; Pinnarelli, Anna; Sorrentino, Nicola; Scarcello, Luigi (Electronics (Basel), 2017)
The interest in the implementation of demand response programs for domestic customers within the framework of smart grids is increasing, both from the point of view of scientific research and from the point of view of real applications through pilot projects. A fundamental element of any demand response program is the introduction at customer level of a device, generally named energy box, able to allow interaction between customers and the aggregator. This paper proposes two laboratory prototypes of a low-cost energy box, suitable for cloud-based architectures for autonomous demand response of prosumers and prosumages. Details on how these two prototypes have been designed and built are provided in the paper. Both prototypes are tested in the laboratory along with a demonstration panel of a residential unit, equipped with a real home automation system. Laboratory tests demonstrate the feasibility of the proposed prototypes and their capability in executing the customers’ loads scheduling returned by the solution of the demand-response problem. A personal computer and Matlab software implement the operation of the aggregator, i.e., the intermediary of the energy-integrated community constituted by the customers themselves, who participate in the demand response program.